Oncogenically active MYD88 mutations in human lymphoma - Ngo, Vu N.; Young, Ryan M.; Schmitz, Roland; Jhavar, Sameer; Xiao, Wenming; Lim, Kian-Huat; Kohlhammer, Holger; Xu, Weihong; Yang, Yandan; Zhao, Hong; Shaffer, Arthur L.; Romesser, Paul; et al. (Nature (London), 2011)
MYD88 signalling in cancer RNA interference screening and high-throughput RNA resequencing have been used to reveal oncogenic mutations in the signalling adapter MYD88 in human lymphomas. One amino acid substitution, L265P, was found in 29% of biopsies from patients with the activated B-cell-like subtype of diffuse large B-cell lymphoma. The same mutation was observed with lower frequency in mucosa-associated lymphoid tissue lymphomas. MYD88 mediates signalling by Toll-like receptors, and the mutations, most of which affect the same amino acid, were shown to activate the pathway and promote cancer cell survival. This study finds frequent mutations in MYD88 in the activated B-cell-like subtype of diffuse large B-cell lymphoma and, with lower frequency, in mucosa-associated lymphoid tissue lymphomas. MYD88 mediates signalling by Toll-like receptors, and the mutations, most of which affect the same amino acid, are shown to activate the pathway and promote cancer cell survival. The activated B-cell-like (ABC) subtype of diffuse large B-cell lymphoma (DLBCL) remains the least curable form of this malignancy despite recent advances in therapy 1 . Constitutive nuclear factor (NF)-κB and JAK kinase signalling promotes malignant cell survival in these lymphomas, but the genetic basis for this signalling is incompletely understood. Here we describe the dependence of ABC DLBCLs on MYD88, an adaptor protein that mediates toll and interleukin (IL)-1 receptor signalling 2 , 3 , and the discovery of highly recurrent oncogenic mutations affecting MYD88 in ABC DLBCL tumours. RNA interference screening revealed that MYD88 and the associated kinases IRAK1 and IRAK4 are essential for ABC DLBCL survival. High-throughput RNA resequencing uncovered MYD88 mutations in ABC DLBCL lines. Notably, 29% of ABC DLBCL tumours harboured the same amino acid substitution, L265P, in the MYD88 Toll/IL-1 receptor (TIR) domain at an evolutionarily invariant residue in its hydrophobic core. This mutation was rare or absent in other DLBCL subtypes and Burkitt’s lymphoma, but was observed in 9% of mucosa-associated lymphoid tissue lymphomas. At a lower frequency, additional mutations were observed in the MYD88 TIR domain, occurring in both the ABC and germinal centre B-cell-like (GCB) DLBCL subtypes. Survival of ABC DLBCL cells bearing the L265P mutation was sustained by the mutant but not the wild-type MYD88 isoform, demonstrating that L265P is a gain-of-function driver mutation. The L265P mutant promoted cell survival by spontaneously assembling a protein complex containing IRAK1 and IRAK4, leading to IRAK4 kinase activity, IRAK1 phosphorylation, NF-κB signalling, JAK kinase activation of STAT3, and secretion of IL-6, IL-10 and interferon-β. Hence, the MYD88 signalling pathway is integral to the pathogenesis of ABC DLBCL, supporting the development of inhibitors of IRAK4 kinase and other components of this pathway for the treatment of tumours bearing oncogenic MYD88 mutations.